Targeted mutation in the neurotrophin-3 gene results in loss of muscle sensory neurons. - Tessarollo, L (1994)
Neurotrophin 3 (NT-3) is one of four related polypeptide growth factors that share structural and functional homology to nerve growth factor (NGF). NT-3 and its receptor, called neurotrophic tyrosine kinase receptor type 3 (Ntrk3; also called TrkC), are expressed early and throughout embryogenesis. We have inactivated the NT-3 gene in embryonic stem (ES) cells by homologous recombination. The mutated allele has been transmitted through the mouse germ line, and heterozygote intercrosses have yielded homozygous mutant newborn pups. The NT-3-deficient mutants fail to thrive and exhibit severe neurological dysfunction. Analysis of mutant embryos uncovers loss of Ntrk3/TrkC-expressing sensory neurons and abnormalities at early stages of sensory neuronal development. NT-3-deficient mice will permit further study of the role of this neurotrophin in neural development.